Nurse Education and Professional Work: Transition Problems? - Kapborg, Inez D; Fischbein, Siv (Nurse education today, 1998)
Eight nursing students kept diaries during their transition from school to professional work. Common problems included management of paperwork, heavy workload, difficulty feeling relaxed when off duty, difficulty in determining what to delegate and when to call for doctors, and tending to seriously ill patients. (SK)